Persons of Pre-Retirement Age in the Labour Market: Employment Problems and Support Measures - Chernykh, Natalya A.; Tarasova, Anna N.; Syrchin, Andrey E. (Economy of Regions, 2020)
The problem of age discrimination in the labour sector has become even more relevant, as the increase in the retirement age and the COVID-19 pandemic in Russia reinforce ageism. The article aims to assess the incidence of age discrimination in the labour market of the Sverdlovsk Region and examine employers’ behaviour towards people nearing retirement. The mixed methodology includes quantitative (analysis of statistics, questionnaire survey, content analysis) and qualitative (in-depth interviews with employers) research methods. While in the 1990s age discrimination was evident and expressed in the exclusion of older workers from the employment sector, now age discrimination is latent and has different manifestations. The results showed that people aged over 45 have less job opportunities in the labour market. Thus, most of them choose to maintain employment. This strategy, however, does not protect against other discriminatory practices such as displacement to less paid positions, reduced pay rate, etc. This situation leads to the decrease in the average wage of workers aged 50-55 by approximately 25 %. We can conclude that employers did not change their behaviour and continue using discriminatory practices to maximise the return on human capital, shifting the risks of pension reform to employees. The government is trying to smooth over the differences between the effectiveness of the regional economic system, focused on maximising the use of regional human resources, and the effectiveness of individual organisations by protecting labour rights and promoting the employment of people nearing retirement. However, the government support measures mainly focus on training or retraining of people aged over 50, while employers lack economic incentives to reconsider their attitude towards older workers. Thus, we recommend developing governmental mechanisms for encouraging employers to change their personnel policy concerning employees aged over 50.